Coplanar waveguide fed stacked dielectric resonator antenna on safety helmet for rescue workers. Issue 2 (21st December 2018) - Das, Saumya; Islam, Hashinur; Bose, Tanushree; Gupta, Nisha
Abstract: This paper presents the design of a compact dielectric resonator antenna for 2.4 GHz wireless local area network or industrial, scientific and medical (ISM) band applications. The antenna consists of four stacked layers of dielectric resonators along with a rigid structure of coplanar waveguide feed. The complete antenna is placed on a safety helmet conformably to develop a wearable system for rescue workers. The achieved −10 dB bandwidth at 2.4 GHz is 6.6% (2.33–2.49 GHz). The maximum gain achieved with this proposed dielectric resonator antenna is 3.74 dBi. "On head performance" of this proposed helmet antenna is also observed including human head model in the simulation.